Improving physics teaching materials on sound for visually impaired students in high school. (1st August 2017) - Toenders, Frank G C; de Putter-Smits, Lesley G A; Sanders, Wendy T M; den Brok, Perry
Abstract: When visually impaired students attend regular high school, additional materials are necessary to help them understand physics concepts. The time for teachers to develop teaching materials for such students is scarce. Visually impaired students in regular high school physics classes often use a braille version of the physics textbook. Previously, we evaluated the physics learning environment of a blind high school student in a regular Dutch high school. In this research we evaluate the use of a revised braille textbook, relief drawings and 3D models. The research focussed on the topic of sound in grade 10.